(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the knowledge, self-care and therapeutic adherence of patients with heart failure, and the impact on hospitalizations. Method: Exploratory, descriptive, prospective, cross-sectional study of a quantitative nature, with 84 patients who answered the heart failure knowledge questionnaire; self-care and therapeutic adherence, after approval by the research ethics committee. Pearson’s Correlation was used to evaluate the correlation between the scales, and linear regression was used for the associated factors. Results: Elderly, male, married, with low education, with arterial hypertension, dyslipidemia, or diabetes, and who underwent angioplasty prevailed. The median ejection fraction was 28%, with moderate or severe symptoms. The score for knowledge of Heart Failure was 7.4 ± 2.2, self-care 43.6 ± 7.0, and Morisky 5.7 ± 1.9. Conclusion: There was no association between the knowledge of heart failure, self-care, and therapeutic adherence scales. There was a correlation between hospitalization with valve etiology diagnoses.